Stevenson’s Careful Observances - Arata, Stephen (Romanticism and Victorianism on the Net, 2007)
AbstractIn his own time, Robert Louis Stevenson was admired as a careful technician of language, a stylist to be put in the company of de Quincey or Pater. In our time, he is known primarily as the author of potboiling plot-driven Gothic tales and adventure yarns. Stevenson himself saw no contradiction in pursuing what Lionel Johnson called his “stylistic nicety and exactitude” in fiction aimed at the mass market, but critics both then and now have largely sidestepped the question of how to reconcile these twin allegiances. In this essay I read The Wrecker (1892), arguably the most densely plotted of Stevenson’s novels, as an extended meditation on the historicity of words. The novel continually calls attention to the “refractive” quality of certain keywords around which the story is structured. At the same time, The Wrecker is concerned with the dynamics of narrativity. It is concerned not just with the procedures by which fictional events are translated into intelligible story, but also with the many ways in which narratives are generated through collaboration: between writers and the literary traditions they work in, between writers and words in their historicity, between writers and their readers—real, imagined, and unforeseen.